Health of (dual) health professional students in German-speaking countries: a scoping review - Ivonne-Nadine Jürgensen; Peter Koch; Annike Morgane Nock; Corinna Petersen-Ewert (Frontiers Media S.A., 2023)
University education marks a new stage in life, which is associated with unknown demands and challenges and can have a negative impact on students' health. Therefore, health promotion in the university setting is becoming increasingly important. In this context, scientific data on the health situation play a crucial role in improving students' health. Thus, the aim of the scoping review was to highlight the current scope of research on the health of health professional students. It also explored problems and outlined key future challenges and solutions. The review was conducted using the Joanna Briggs Institute (JBI) methodology for a scoping review. A total of nine databases (PubMed, CINAHL, CareLit, LIVIVO, Scopus, Psyndex, PEDro, OTseeker, Google Scholar) were systematically searched. The following search criteria were defined: health professional students, health, Germany, German-speaking countries, all types of sources from 2012 to present are selected. The research studies were mapped in a table and health evidence of included studies was summarized narratively. The initial search resulted in 23,938 records. Seven records met the inclusion criteria and were included in the review. Six cross-sectional studies were conducted in Germany, and one cross-sectional study was conducted in Switzerland. In fact, one study included a representative population. Qualitative studies were not found. The most studies investigated health status, health behavior, and personal resources. Most of the studies examined female nursing students. The included studies indicated that the young students reported physical or mental health conditions. In addition, the studies also identified health resources of the students that need to be improved. In summary, there is currently limited health evidence on this group of students in German-speaking countries. Therefore, further research is needed to generate knowledge and comprehensively describe the health situation.